HUBUNGAN ANTARA PENGUASAAN KOSAKATA (WORTSCHATZ) DENGAN KEMAMPUAN MEMBACA MEMAHAMI (LESEVERSTEHEN) TEKS BAHASA JERMAN SISWA KELAS XI - Mawaresna, Anis; Anwar, Muh (Universitas Negeri Makassar, 2020)
Abstract. This study aims to obtain data and information about the relationship between vocabulary mastery and reading comprehension skills of students in class XI SMA Negeri 1 Palopo. This research is descriptive. The population of this study was all students of class XI, totaling six classes with a total of 208 students. The sample of this research is class XI IPA 3, amounting to 25 students selected through a random sampling technique. The research data were collected through a written test and analyzed using the Product Moment correlation. The result of rcount = (0.411)> rtable = (0.396). The results of the data analysis show that there is a significant relationship between vocabulary mastery and reading comprehension skills of students in class XI SMA Negeri 1 Palopo.